The Convergence of Some Products in the Adams Spectral Sequence - Wang, Yuyu; Wang, Jianbo (Mathematica Scandinavica, 2015)
In this paper, we will use the family of homotopy elements ζ_nπ_*S, represented by h_0b_nExt_A^3,p^n+1 q+q(Z_p, Z_p) in the Adams spectral sequence, to detect a ζ_n-related family γ_s+3β_2ζ_n-1 in π_*S. Our main methods are the Adams spectral sequence and the May spectral sequence, here prime p≥ 7, n>3, q=2(p-1).